2021
DOI: 10.3389/fimmu.2021.656350
|View full text |Cite
|
Sign up to set email alerts
|

Lung Neutrophilic Recruitment and IL-8/IL-17A Tissue Expression in COVID-19

Abstract: The new SARS-CoV-2 virus differs from the pandemic Influenza A virus H1N1 subtype (H1N1pmd09) how it induces a pro-inflammatory response in infected patients. This study aims to evaluate the involvement of SNPs and tissue expression of IL-17A and the neutrophils recruitment in post-mortem lung samples from patients who died of severe forms of COVID-19 comparing to those who died by H1N1pdm09. Twenty lung samples from patients SARS-CoV-2 infected (COVID-19 group) and 10 lung samples from adults who died from a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
25
3
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 40 publications
4
25
3
1
Order By: Relevance
“…These findings were in line with the study conducted by Li Y et al [33]; and could lead to more common acute upper respiratory tract symptoms in hospitalized H1N1 patients [34]. A study conducted by Azevedo et al further confirmed this phenomenon; in which tissue expression increasing of IL-8/IL-17A and a higher number of neutrophils were identified in samples from the H1N1 group compared to the COVID-19 group [35]. The diverse characteristics of infection provides the rationale for advancing differential treatment efforts to improve outcomes of these two types of patients.…”
Section: Plos Neglected Tropical Diseasessupporting
confidence: 89%
See 1 more Smart Citation
“…These findings were in line with the study conducted by Li Y et al [33]; and could lead to more common acute upper respiratory tract symptoms in hospitalized H1N1 patients [34]. A study conducted by Azevedo et al further confirmed this phenomenon; in which tissue expression increasing of IL-8/IL-17A and a higher number of neutrophils were identified in samples from the H1N1 group compared to the COVID-19 group [35]. The diverse characteristics of infection provides the rationale for advancing differential treatment efforts to improve outcomes of these two types of patients.…”
Section: Plos Neglected Tropical Diseasessupporting
confidence: 89%
“…Ct values at admission were lower in co-infected patients (median 32 [25.5-35.5]) than patients with SAR-CoV-2 monoinfection (median 36 [32][33][34][35][36][37][38]) (Fig 1), indicating higher initial viral load in co-infected patients. In the subsequent monitoring, the Ct value of the two groups have been increasingly similar.…”
Section: Analysis Of Distribution Regulation Of Ct Valuesmentioning
confidence: 99%
“…These cytokines increase vascular permeability and allow the intense neutrophilic infiltrates to give a response to viral infection. A study indicated the G allele of rs3819025 correlated with higher tissue expression of IL-17A in the COVID-19 cases [46]. In our study, serum IL17 levels of all COVID-19 cases, whether they received vitamin D supplementation or not, remained low compared with controls.…”
Section: Vitamin D and Covid-19supporting
confidence: 40%
“…As seen in COVID-19, the innate immune response stimulates the release of both pro-inflammatory and anti-inflammatory cytokines in response to viral and bacterial infections [2]. Vitamin D levels are associated with cytokines such as IL-1, IL-6, IL-10, and TNFα [5]; additionally, vitamin D can reduce pro-inflammatory TH1 cytokines such as TNFα and IFNg, and increase anti-inflammatory cytokines released from macrophages [45][46][47]. In this respect, it is known that it can also regulate the adaptive immune response [14].…”
Section: Vitamin D and Covid-19mentioning
confidence: 99%
“…Among its functions, IL-8 contributes to induce endothelial permeability by inducing the expression of integrins, enabling neutrophils to pass through vessels to reach inflammation sites [38] and preventing clot formation [39].…”
Section: Discussionmentioning
confidence: 99%